PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. BUSSAN AUTO FINANCE (BAF) DI PALU - Arafah, Moh; Sandriana Putri, Ni Made (Fakultas Ekonomi Universitas Alkhairaat, 2023)
The purpose of this study was to determine how much influence leadership and work motivation have on employee performance, either simultaneously or partially. The data analysis method in this research uses multiple linear regression analysis. The results of this research indicate that leadership and work motivation simultaneously have a significant effect on employee performance at PT. Bussan Auto Finance (BAF) in Palu City. Partially, leadership obtains a significant value for the influence of X1 on Y, which is 0.004 <0.05 and tcount 3.011 > ttable 2.00758, so it can be concluded that H1 is accepted, which means there is an influence of X1 on Y. and the variable Work Motivation obtained a significant value for the effect of X2 on Y which is 0.005 <0.05 and the tcount value is 2.921 > 2.00758, so it can be concluded that H2 is accepted, which means that there is an effect of X2 on Y. Keyword: Leadership, Work Motivation, and Employee Performance